2015
DOI: 10.1371/journal.pone.0117081
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Inhibits the Differentiation of T Helper 17 Cells through mTOR/STAT3 Signaling Pathway

Abstract: Enhanced activity of interleukin 17 (IL-17) producing T helper 17 (Th17) cells plays an important role in autoimmune and inflammatory diseases. Significant loss of body weight and appetite is associated with chronic inflammation and immune activation, suggesting the cross talk between immune and neuroendocrine systems. Ghrelin has been shown to regulate the organism immune function. However, the effects of ghrelin on the differentiation of Th17 cells remain elusive. In the present study, we observed the enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…To delineate the potential mechanism underlying IL-17/IL-17R-induced autophagy, the activation status of JAK2 and STAT3 under the interference of IL-17/IL-17R was observed. It was found that IL-17/IL-17R increased the phosphorylation of JAK2 and STAT3, which was consistent with the fact that STAT3 controls Th17 cell differentiation (54). Previous studies have shown that the PI3K signaling pathway has a crucial role in autophagy (55)(56)(57).…”
Section: Discussionsupporting
confidence: 77%
“…To delineate the potential mechanism underlying IL-17/IL-17R-induced autophagy, the activation status of JAK2 and STAT3 under the interference of IL-17/IL-17R was observed. It was found that IL-17/IL-17R increased the phosphorylation of JAK2 and STAT3, which was consistent with the fact that STAT3 controls Th17 cell differentiation (54). Previous studies have shown that the PI3K signaling pathway has a crucial role in autophagy (55)(56)(57).…”
Section: Discussionsupporting
confidence: 77%
“…The differential ghrelin physiology in control and H. pylori -infected mice that we observed, consistent with prior studies (Bercik et al, 2009), provides further evidence of the systemic effects of gastric H. pylori. The anti-inflammatory properties of ghrelin, inhibiting Th17 cell differentiation (Xu et al, 2015), might partially explain why when levels are high (3-months), pulmonary Th17 populations are not significantly elevated. This hormonal interaction may provide H. pylori with additional means for evading host immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in agreement with recent literature reporting a specific effect of ghrelin on both Th1 and Th17 expansion at steady state and during systemic inflammation in mice. 11,42,43 In particular, potent therapeutic effects of ghrelin have been recently described in a mouse model of EAE, in which autoimmune reaction is involved in the disease development. Souza-Moreira et al have shown that systemic treatment with ghrelin, after the disease onset, reduced clinical severity of EAE via specifically acting on the expansion of encephalitogenic Th1 and Th17.…”
Section: Discussionmentioning
confidence: 99%